Pendidikan seksual remaja pada keluarga Bugis di Kabupaten Sinjai - Hasni Hasni; A. Octamaya Tenri Awaru (Seminar Nasional LP2M UNM, 2019)
This research was conducted in Sinjai District which aimed to find out the forms of sexual education received by adolescents in the Bugis Sinjai family and how the children of Bugis Sinjai tribal teenagers responded in receiving sexual education from their parents. This type of research uses descriptive qualitative research. The research informants were selected by purposive sampling, the number of informants was 10 teenagers with the criteria of high school students, originating from the tribal family of Bugis and aged 16-18 years. Data collection used is interviews, observation and documentation. The results of this study indicate 1) the forms of sexual education received by adolescents in the Bugis family in Sinjai Regency are 4, namely: Introducing differences and functions of sexual organs, gender roles, relationships with the opposite sex, and puberty. Teenage parents in the Bugis family have not provided knowledge about intercourse because they consider this to be discussed later after the marriage. 2) The response given by adolescents to the Bugis family in Sinjai District in receiving a positive response sexual education because the conducive time apart from the results of the study found that children are happy because parents always care about the children so that the children are enthusiastic when the children are invited to discuss sexual issues. As for when the child has a negative response because the child is tired or the moment is not right. Overall the teenage family of Bugis accepts sex education with open arms and considers this as a form of parental concern for them